A novel SRY gene mutation c.266 A>T (p.E89V) in a 46, XY complete gonadal dysgenesis patient. (30th July 2019) - Raveendran, Suresh Kumar; Ramachandran, Lola; Joseph, Lincy; Asokan, Aneesh Kumar; Raj, Soumya; George, Alex; James, Jimcy
Abstract: The SRY gene is considered as the key player in the male sexual differentiation and developmental pathway. SRY gene mutations account for ~15% of 46, XY disorders of sexual development patients, and majority of them resides within the HMG domain of the protein. In this study, we report a novel missense mutation within the HMG domain of SRY gene, and an A‐to‐T transition causes E89V amino acid substitution in a 15‐year‐old female patient with 46, XY karyotype and complete gonadal dysgenesis. Moreover, three‐dimensional analysis of protein–DNA complex showed that the replacement of highly hydrophilic glutamic acid residue with a hydrophobic residue like valine would have an impact on the structure of protein. In conclusion, we identified a novel SRY mutation in a 46, XY female patient with complete gonadal dysgenesis, and based on the protein modelling, we propose that the identified mutation could impair normal function of the SRY protein.